Ethnomedicines used by Kaniyakaran tribes in Kaniyakumari district-Southern Western Ghats of Tamil Nadu, India - R. Pushpakarani and S. Natarajan (Journal of Applied Pharmaceutical Science, 2014)
A survey was carried out among the Kani tribals in Kaniyakumari district- Southern Western Ghats, of Tamil Nadu, India. Traditional uses of 62 plant species belonging to 34 families are described under this study. In this communication, the informations got from the rural inhabitant were compared with the already existing literature. The medicinal plants were mostly used to cure asthma, rheumatoid arthritis, skin and sex related diseases. The medicinal plants used by people are arranged alphabetically followed by Botanical name, family, Voucher specimen number, Local name, Part used, mode of preparation.
Keywords: Ethnomedicines, Kani tribals, Medicinal plants, Southern western Ghats.